2013
DOI: 10.1136/bcr-2013-009604
|View full text |Cite
|
Sign up to set email alerts
|

A regenerative approach towards mucosal fenestration closure

Abstract: Mucosal fenestration is an opening or an interstice through the oral mucosa. A lesion which occurs with greater frequency than generally realised, its occurrence is attributed to a myriad of causes. Mucogingival procedures including connective tissue grafts, free gingival grafts and lateral pedicle grafts are generally considered to be the treatment of choice in the closure of a mucosal fenestration. More often, these procedures are performed in conjunction with other procedures such as periradicular surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Apical surgery was performed for all cases with or without prior non-surgical root canal (re)treatment, except for 1 as reported by Gandi et al ( 17 ) where a flap was raised to gain access to the apical region, and degranulation and root debridement was performed with no reported root-end resection. Surgical intervention revealed that 9 out of the 24 teeth with mucosal fenestrations involving the root apex were associated with bony dehiscences (37.5%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apical surgery was performed for all cases with or without prior non-surgical root canal (re)treatment, except for 1 as reported by Gandi et al ( 17 ) where a flap was raised to gain access to the apical region, and degranulation and root debridement was performed with no reported root-end resection. Surgical intervention revealed that 9 out of the 24 teeth with mucosal fenestrations involving the root apex were associated with bony dehiscences (37.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with apical fenestrations associated with endodontic pathologies may present with various complaints, signs and symptoms. These include traumatic dental injuries ( 14 , 17 ), aesthetic concerns ( 16 , 28 ), gingival defects or discomfort ( 11 , 16 , 17 , 20 ) and pain, especially on palpation and mastication ( 3 , 12 , 13 ). Patients may develop a habit of rubbing the area of discomfort, which could exacerbate their symptoms ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although the etiology for GFs is unclear, putative factors that have been shown to be associated with GFs include plaque/calculus, cervical enamel projections, trauma, tooth malpositioning, occlusal factors, factitious habits, and iatrogenesis. 4,5 Although some GF lesions can be managed nonsurgically with monitoring and meticulous oral hygiene, surgical correction involving various periodontal plastic surgical procedures is preferred. 2 Successful treatment of GF by connective tissue grafting, 3,4 acellular dermal matrix allograft, 6 and regenerative approaches, 7,8 have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the fenestration lesion may become vulnerable to plaque and calculus accumulation, dentinal hypersensitivity, and compromise the esthetics and periodontal stability of the affected tooth 3 . Although the etiology for GFs is unclear, putative factors that have been shown to be associated with GFs include plaque/calculus, cervical enamel projections, trauma, tooth malpositioning, occlusal factors, factitious habits, and iatrogenesis 4,5 …”
Section: Introductionmentioning
confidence: 99%